Promoting perioperative advance care planning: a systematic review of advance care planning decision aids. (November 2015) - Aslakson, Rebecca A; Schuster, Anne LR; Reardon, Jessica; Lynch, Thomas; Suarez-Cuervo, Catalina; Miller, Judith A; Moldovan, Rita; Johnston, Fabian; Anton, Blair; Weiss, Matthew; Bridges, John FP
This systematic review identifies possible decision aids that promote perioperative advance care planning (ACP) and synthesizes the available evidence regarding their use. Using PubMed, EMBASE, Cochrane, SCOPUS, Web of Science, CINAHL, PsycINFO and Sociological Abstracts, researchers identified and screened articles for eligibility. Data were abstracted and risk of bias assessed for included articles. Thirty-nine of 5327 articles satisfied the eligibility criteria. Primarily completed in outpatient ambulatory populations, studies evaluated a variety of ACP decision aids. None were evaluated in a perioperative population. Fifty unique outcomes were reported with no head-to-head comparisons conducted. Findings are likely generalizable to a perioperative population and can inform development of a perioperative ACP decision aid. Future studies should compare the effectiveness of ACP decision aids.